Evaluating the Key Factors of Successful Implementation of World Class Manufacturing Using an Integrated Approach of Interpretive Structural Modeling(ISM), Graph Theory and Matrix Approach (GTMA): A Case Study for Iran Khodro and Saipa in Iran - akbar Alem Tabriz; hamid reza Talaie; elnaz Moradi (مدیریت صنعتی, 2013)
World Class Manufacturing (WCM) is a key concept in the contemporary world that has attracted the attention of many industries. Many of the organizations in order to compete in the global market use world class manufacturing system. There are different views about the philosophy and concepts of WCM features, but what is considered as a key element is to achieve performance consistent with the "best in the world". Many factors that contribute to the successful implementation of world class manufacturing have been identified, but a little research on the evaluation of these factors has been done in developing countries. The main objective of this paper is to present a technique that assesses key factors of the successful implementation of world class manufacturing and shows the impact of these factors on the implementation of world class manufacturing in the form of a numeric index that is attributed to the organization. This technique combines two approaches that are interpretive structural modeling (ISM), graph theory and matrix approach (GTMA). Also, the numerical index of the technique provides the capable of comparing and ranking organizations in terms of the WCM implementation. To implement this technique in two automobile companies (Iran Khodro and Saipa) important factors in the implementation of world-class Manufacturing have been identified and assessed